(untitled) (Journal of Nepal Geological Society, 2002)
Sacred religious monuments such as chorten, and stone-walls (carved with religious inscriptions) can be found all along the Himalaya in and around villages dominated by Buddhist population. These structures are found to have been erected not only around monasteries and other holy places, but also in areas where mountain hazards such as torrent, debris flow and snow avalanche occur. Careful observation of the location of these structures indicate that they were erected also to serve as indicators, silent witnesses and even to protect settlements and farmland from hazards. The reason why this practice is typical for the Buddhistic-Lamaistic region of the Himalaya must partly be due to a wide prevalence of various hazardous geomorphological processes occurring within the Higher Himalaya and Trans Himalayan valleys, which forms the homelands of the Tibetan culture. The position of the sacred structures may be used as a good indicator for the past hazardous events that occurred at a certain time. Some structures also seem to have been built for only a symbolic value. Thus their position can be used for finding or delimiting areas, which may fall in the "red zone" on mapping mountain hazards.